The effect of liquidity risk on financial performance Applied study on banks listed on the Damascus stock exchange (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This study aims to analyze the impact of liquidity risks on financial performance (return on assets, return on equity), in order to determine the size of potential risks that banks may be exposed to and its impact on the performance of banks listed on the Damascus Stock Exchange. analytical and measurable data during the time period extending from 2010 to 2020, based on cross sectional time series (through the application of three models: the aggregate regression model, the fixed effects model, and the random effects model), and this study reached a set of results, the most important of which are the following: That there is no effect of liquidity risk on financial performance (return on assets), in addition to that there is no effect of liquidity risk on financial performance (return on equity), as long as the result of testing the hypothesis is not statistically significant, the researcher presented a set of recommendations, the most important of which are: Conducting other related research to study the impact of other variables on the dependent variable (financial performance), and the researcher also recommends introducing modified variables on the relationship between the independent variable, liquidity risk, and the dependent variable, performance, as an attempt to reach optimal results that may benefit the banks under study in particular, and other banking environments in general.